The semantic depth of Japanese-English bilingual children - Hayes, Richy Lewis; Kan, Pui Fong (Frontiers in Language Sciences, 2025)
This study examined semantic organization in Japanese-English bilingual children, focusing on the syntagmatic-paradigmatic shift, cross-linguistic relationships between syntagmatic and paradigmatic associations, and the influence of lexical diversity on semantic organization. Participants were 30 Japanese-English bilingual children aged 2 to 8 (M = 70.8, SD = 22.14). A Word Association Task (WAT) assessed semantic knowledge in both languages, with responses coded for type, errors, and code switching. Lexical diversity (Number of different words) was measured using the Multilingual Assessment Instrument of Narratives (MAIN), and language input was measured using a questionnaire. Regression models revealed: No evidence of a syntagmatic-paradigmatic shift, but a gradual increase in both syntagmatic/paradigmatic responses with age and lexical diversity; and proficiency in generating paradigmatic and syntagmatic responses in one language predicted proficiency in the other, controlling for age and language input. This study highlights cross-linguistic influences in Japanese-English bilingual children's semantic organization, with implications for educators emphasizing the beneficial impact of language instruction in one language on the other.